Interest rate and loan supply: Islamic versus conventional banking system - Liza Marwati Mohd Yusoff; Aisyah Abdul Rahman; Norazlan Alias (Penerbit Universiti Kebangsaan Malaysia, 2001)
This paper attempts to explore the effect of interest rate on loan supply of Islamic banking and Conventional banking system. The analysis segregated the Islamic and Conventional banking system into commercial bank, finance company and merchant bank. Overnight and 3 month Klibor are used as interest proxy. Unit root test, Granger Causality test, Akaike Information Criterion and Regression analysist are used in the study. The results of Granger Causality test indicate that the growth of overnight Klibor causes changes in the growth of Islamic and Conventional loan of Merchant Banks significantly and from the regression analysis, it is confirm that Islamic and Conventional loan growth of merchant bank are significantly positive related to overnight Klibor.